Temporal-spatial correlation between angiogenesis and corticogenesis in the developing chick optic tectum - Rodriguez Celin, Alejandra Jimena (2015)
The developing chick optic tectum is a widely used model of corticogenesis and angiogenesis. Cell behaviors involved in corticogenesis and angiogenesis share several regulatory mechanisms. In this way the 3D organizations of both systems adapt to each other. The consensus about the temporally and spatially organized progression of the optic tectum corticogenesis contrasts with the discrepancies about the spatial organization of its vascular bed as a function of the time. In order to find out spatial and temporal correlations between corticogenesis and angiogenesis, several methodological approaches were applied to analyze the dynamic of angiogenesis in the developing chick optic tectum. The present paper shows that a typical sequence of developmental events characterizes the optic tectum angiogenesis. The first phase, formation of the primitive vascular bed, takes place during the early stages of the tectal corticogenesis along which the large efferent neurons appear and begin their early differentiation. The second phase, remodeling and elaboration of the definitive vascular bed, occurs during the increase in complexity associated to the elaboration of the local circuit networks. The present results show that, apart from the well-known influence of the dorsal-ventral and radial axes as reference systems for the spatial organization of optic tectum angiogenesis, the cephalic-caudal axis also exerts a significant asymmetric influence. The term cortico-angiogenesis to describe the entire process is justified by the fact that tight correlations are found between specific corticogenic and angiogenic events and they take place simultaneously at the same position along the cephalic-caudal and radial axes.